Studying Well and Performing Well: A Bayesian Analysis on Team and Individual Rowing Performance in Dual Career Athletes - Gavala-González, Juan; Martins, Bruno; Ponseti, Francisco Javier; Garcia-Mas, Alexandre (Frontiers in Psychology, 2020)
On many occasions, the maximum result of a team does not equate to the total maximum individual effort of each athlete (social loafing).Athletes often combine their sports life with an academic one (Dual Career), prioritizing one over the over in a difficult balancing act. The aim of this research is to discover both the existence of social loafing in a group of novice university rowers and the differences that exist according to sex, academic performance and the kind of sport previously practiced (individual or team). Therefore, a study was conducted from a probabilistic perspective using the Bayesian Network analysis methodology. The results confirm the existence of the Ringelmann effect or social loafing. The Bayesian analysis let us confirm that having a good student who practices a team sport, even in the individual rowing concept, increases the probability of obtaining greater performance (higher number of strokes and more power in each one).Therefore, when rowing partnerships are formed, the occurrence probability chain is quickly simplified, along with values of the top and bottom variables. Finally, the instantiations undertaken on the bottom variable that appears to be common in the two BNs, the watt input, enhance the results obtained.